Associations between total protein, globulin, and nasal Methicillin-Resistant Staphylococcus aureus (MRSA) colonization in US adults: results from the national health and nutrition examination survey 2001–2004 - Chen, Kanchao; Feng, Xiaomeng; Liu, Futong; Fan, Yuping; Zhang, Tingting; Wang, Hui; Feng, Sizhou (Frontiers in Immunology, 2025)
ObjectiveThere is limited evidence on the association between total serum protein (TP), serum globulin (GLB), and Methicillin-Resistant Staphylococcus aureus (MRSA) nasal colonization. The purpose of this study was to investigate the association between TP, GLB, and MRSA nasal colonization in US adults with data derived from the National Health and Nutrition Examination Survey (NHANES).MethodsUsing NHANES 2001–2004 data, we employed propensity score matching (PSM) to control confounders, weighted logistic regression to evaluate associations of TP and GLB with MRSA colonization, restricted cubic splines (RCS) for non-linear analysis, and subgroup and sensitivity analyses for validation.ResultsAmong 7,585 adults, 1.31% (n = 99) had MRSA nasal colonization. Adjusted multivariable regression identified TP and GLB as independent protective factors (TP: OR=0.92, 95%CI 0.88–0.96; GLB: OR=0.91, 95%CI 0.86–0.97; p< 0.05 for all). Categorizing TP and GLB into quartiles (Q4 vs. Q1) reinforced this association (TP: OR=0.21, 95%CI 0.07–0.59; GLB: OR=0.28, 95%CI 0.12–0.67; p< 0.05 for all) with consistent results post-PSM. Restricted cubic splines confirmed dose-dependent negative correlations. Subgroup analyses and sensitivity analyses supported the robustness of these findings.ConclusionThere was a negative correlation between TP, GLB, and MRSA nasal colonization in participants aged 18 years or older. Our data support the protective role of TP and GLB in MRSA colonization, and the specific mechanisms of these biomarkers in MRSA colonization and their clinical implications require further investigation.